2015
DOI: 10.4236/arsci.2015.34012
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA Fragmentation in Patients with Infertility in Dakar (Senegal)

Abstract: The presence of DNA fragmentation in semen is associated with poor results in ART (Assisted Reproductive Technology). This has led to the introduction of sperm DNA integrity testing in the clinical assessment of male infertility. The TUNEL assay is one of the most commonly used tests to measure DNA fragmentation in research studies, but it is now being optimized for routine clinical use. So, the objectives of our study were to install the TUNEL assay in our laboratory and to use it to assess the degree of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Our results are consistent with the studies (Sergerie et al, 2005) [ 25 ] that found a DFI in the infertility group was significantly higher than in the fertile group (40.9 ± 14.3% compared to 13.1 ± 7.3%) and the mean sperm concentration in the infertile group was also significantly lower compared to the fertile group (62.9 ± 33.2 × 10 6 /ml compared to 102.4 ± 66.4 × 10 6 /ml). DFI can be used to distinguish infertile men from fertile men [ 26 ]. A man with DFI sperm ≥ 26.1% has 2.84 times higher risk for infertility than the male with DFI sperm of < 26.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the studies (Sergerie et al, 2005) [ 25 ] that found a DFI in the infertility group was significantly higher than in the fertile group (40.9 ± 14.3% compared to 13.1 ± 7.3%) and the mean sperm concentration in the infertile group was also significantly lower compared to the fertile group (62.9 ± 33.2 × 10 6 /ml compared to 102.4 ± 66.4 × 10 6 /ml). DFI can be used to distinguish infertile men from fertile men [ 26 ]. A man with DFI sperm ≥ 26.1% has 2.84 times higher risk for infertility than the male with DFI sperm of < 26.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we described the setting up of this protocol in our laboratory. We found a cut-off of 15% with an accuracy of 72.1% [15] to differentiate infertile men with DNA damage from healthy men.…”
Section: Tunel Assay For Measurement Of Sperm Dna Fragmentationmentioning
confidence: 85%
“…The spermatozoon were then washed and resuspended in a (methanol/acetic acid) mixture and stored at -20˚C until run time (Carnoy II solution). The test was performed according to the protocol of our laboratory [15]. To permeabilize cells, we used a solution of Triton.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm DFI was significantly higher in patients with infertility compared to those of control (22.2±5.6% vs. 16.7±0.7%; p<0.05). From these results, it may be concluded that sperm DFI determination could be used to distinguish infertile men from fertile men (Diallo et al, 2015). Thus, it may be concluded that a man with sperm DFI of≥26.1% has 2.84 times greater risk for infertility than men with sperm DFI of<26.1%.…”
Section: Assessment Of Sperm Dna Fragmentation (Df)mentioning
confidence: 91%